Enhancing PVT performance with triangular tubes: A numerical study on Bi-fluid cooling efficiency gains - Ehab M. Almetwally; Abdelkrim Khelifa; Mohammed El Hadi Attia; Abd Elnaby Kabeel; Moataz M. Abdel-Aziz (Case Studies in Thermal Engineering)
Hybrid PVT systems are emerging as a key solution to improve solar energy utilization by simultaneously generating electricity and recovering thermal energy. This study presents a numerical investigation of a hybrid photovoltaic-thermal (PVT) system enhanced by a bi-fluid cooling mechanism, combining water and air to optimize thermal and electrical performance. The system integrates 16 triangular tubes beneath a 54 cm × 120 cm PV panel (4 × 8 cells), with water circulating at 0.0025 kg/s and natural air flow for enhanced cooling. Simulations were conducted using meteorological data from a representative day in Algeria, from 7:00 to 18:00, with solar irradiance varying from 114.71 to 995.57 W/m2 and ambient temperatures ranging from 306.05 to 318.13 K. The bi-fluid cooling system demonstrated superior performance, achieving an average thermal efficiency of 41.10 % - an 80.65 % improvement over conventional PVT systems. Peak thermal power outputs reached 292.53 W (water) and 92.28 W (air), with maximum outlet temperatures of 327.98 K (water) and 322.85 K (air). Electrical efficiency improved to 14.93 % while maintaining PV module temperatures at an average of 326.26 K. The system's total thermal power output averaged 200.42 W throughout the day. These results highlight the effectiveness of combined water-air cooling in Algerian conditions, where high solar irradiance and ambient temperatures typically challenge PV performance. The study provides valuable insights for optimizing PVT systems in similar semi-arid climates, demonstrating significant potential for practical solar energy applications. The proposed bi-fluid PVT configuration offers a scalable and efficient pathway for solar energy harvesting in hot regions, with strong implications for sustainable building applications.